Which Better between Dynasties or Military Regent on Financial Independence Ratio?: Empirical Studies in East Java - Hady, Aufar; Mudhaffar, Muhammad Aqil (ProBisnis : Jurnal Manajemen, 2025)
This study aims to investigate the effect of political dynasties and military regents on the Regional Finance Independence Ratio in East Java, Indonesia. By using panel dataset from 2008–2024 across 38 districts/cities, We  employs a panel regression model to test the effect of leadership background on the Financial Independence Ratio (FIR). The findings show that regent with political dynasties can reduce Regional Financial Independence. But, there is no evidence that Regent with military-background impact on it. Our findings also show that regent with Political Dynaties is more destructive that Military Background regent. This results highlight the need for anti-dynasty safeguards, transparency measures, and PAD-oriented reforms to strengthen local fiscal independence, while military backgrounds appear less consequential in shaping fiscal outcomes.